An Analysis of the Use of the MyPertamina Application in Reducing the Misuse of Government-Subsidised Pertalite (A Literature Review) - Putra, Juniawan Mandala; Menorizah, Menorizah (JERIT: Journal of Educational Research and Innovation Technology, 2025)
Fuel subsidies remain one of the government’s key policy instruments to safeguard public purchasing power; however, their implementation frequently faces problems of mistargeting and misuse. Pertalite, as one of the subsidised fuel types, is disproportionately consumed by higher-income groups, thereby reducing the effectiveness of the subsidy’s original intent. In response, the government, through PT Pertamina, introduced the Subsidi Tepat programme, supported by the MyPertamina application and a QR Code system, in order to enhance transparency, accountability, and accuracy in the distribution of subsidised fuel. This study aims to analyse the effectiveness of MyPertamina in reducing the misuse of subsidised Pertalite, to identify the challenges encountered, and to propose relevant policy recommendations. The research employs a literature review method, drawing upon academic studies and official reports from 2021 to 2025. The findings indicate that MyPertamina has made a positive contribution through the digitalisation of transactions, enabling real-time recording, with data showing that by 2024, 93.9% of Pertalite transactions had been digitalised. This development strengthens transparency in distribution and supports the monitoring of subsidy quotas. Nevertheless, the study also reveals significant limitations, including technical barriers related to infrastructure, low levels of digital literacy, public resistance, and the potential for misuse through QR code lending and the use of registration brokers. Sentiment analysis of users even shows that the majority of reviews were negative, highlighting the need for improvements in user experience and public communication. In conclusion, while MyPertamina plays a strategic role in promoting more targeted distribution of subsidised fuel, its success remains heavily dependent on the reinforcement of regulatory frameworks, public education, the strengthening of digital infrastructure, and layered supervision. These recommendations are expected to enhance the governance of energy subsidies in Indonesia, ensuring that they are more equitable, efficient, and sustainable